Human sperm proteome reveals the effect of environmental borne seminal polyaromatic hydrocarbons exposome in etiology of idiopathic male factor infertility - Nayak, Jasmine; Jena, Soumya Ranjan; Kumar, Sugandh; Kar, Sujata; Dixit, Anshuman; Samanta, Luna (Frontiers in Cell and Developmental Biology, 2023)
Polyaromatic hydrocarbons (PAHs) are considered as redox active environmental toxicants inducing oxidative stress (OS) mediated injury to cells. Oxidative predominance is reported in 30-80% of idiopathic male infertility (IMI) patients. Hence, this work aims to unravel correlation, if any, between seminal PAH exposome and sperm function in IMI patients through a proteomic approach. Seminal PAH exposome was analyzed in 43 fertile donors and 60 IMI patients by HPLC and receiver operator characteristic (ROC) curve was applied to find out the cut-off limits . Spermatozoa proteome was analyzed by label free liquid chromatography mass spectroscopy (LC-MS/MS) followed by molecular pathway analysis using bioinformatic tools. Validation of key proteins’ expression and protein oxidative modifications were analyzed by western blot. Of the 16 standards toxic PAH, 13 were detected in semen. Impact of the different PAHs on fertility are Anthracene